(3JaSjQ GdbQBfs - (3efUhQ Hf eMeO Hf YHO GdLHGQ GdSeYGfj GdTGaYj, CHh efUhQ , LeGd GdOjf J (B562 (3g` s
(3ChdgG (B:s
(3jHOC ShQI jhfS(B: (3hgj ecjI GdGKdGK BjGJ hbhdg JYGdi(B" (3aEf cfJ ai Tc(B" s
(3BNQgG (B:s
(3jYfi ai GdBNQI Je GdLRA GdKGfi ef JaSjQ GdSeYGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B136) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs